2004
DOI: 10.1136/qhc.13.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Use of medical emergency team responses to reduce hospital cardiopulmonary arrests

Abstract: Background: Medical emergency team (MET) responses have been implemented to reduce inpatient mortality, but data on their efficacy are sparse and there have been no reports to date from US hospitals. Objectives: To determine how the incidence and outcomes of cardiac arrests have changed following increased use of MET. Methods: Objective criteria for MET activation were created and disseminated as part of a crisis management program, after which there was a rapid and sustained increase in the use of MET. A retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
1
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(142 citation statements)
references
References 16 publications
1
135
1
4
Order By: Relevance
“…220,221,224,225,[227][228][229][230][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247]249,250,[253][254][255][256] For the 1 RCT, 218 no significant difference between control hospitals and intervention hospitals, both unadjusted (P=0.306; Diff, −0.208; 95% CI, −0.620 to 0.204) and adjusted (P=0.736; OR, 0.94; 95% CI, 0.79-1.13), was demonstrated. Of the 31 observational studies reporting on cardiac arrest rates, 1 before-after study using an aggregated weighted scoring system (Modified Early Warning Score [MEWS]) reported significantly higher cardiac arrest rates in MEWS bands 3 to 4 after intervention, but not in MEWS bands 0 to 2 or 5 to 15, and overall cardiac arrest rate significance was not reported 232 ; 7 studies with no adjustment demonstrated no significant improvement in cardiac arrest rates after the introduction of a MET system 224,225,[228][229][230]233,234 ; 15 studies with no adjustment demonstrated significant improvement in cardiac arrest rates after the introduction of a MET system 220,221,…”
Section: Consensus On Sciencementioning
confidence: 99%
“…220,221,224,225,[227][228][229][230][232][233][234][235][236][237][238][239][240][241][242][243][244][245][246][247]249,250,[253][254][255][256] For the 1 RCT, 218 no significant difference between control hospitals and intervention hospitals, both unadjusted (P=0.306; Diff, −0.208; 95% CI, −0.620 to 0.204) and adjusted (P=0.736; OR, 0.94; 95% CI, 0.79-1.13), was demonstrated. Of the 31 observational studies reporting on cardiac arrest rates, 1 before-after study using an aggregated weighted scoring system (Modified Early Warning Score [MEWS]) reported significantly higher cardiac arrest rates in MEWS bands 3 to 4 after intervention, but not in MEWS bands 0 to 2 or 5 to 15, and overall cardiac arrest rate significance was not reported 232 ; 7 studies with no adjustment demonstrated no significant improvement in cardiac arrest rates after the introduction of a MET system 224,225,[228][229][230]233,234 ; 15 studies with no adjustment demonstrated significant improvement in cardiac arrest rates after the introduction of a MET system 220,221,…”
Section: Consensus On Sciencementioning
confidence: 99%
“…This system was first instituted in the early 1990s to reduce the incidence of and mortality from cardiac arrests and other severe conditions in hospitals (Lee, Bishop, Hillman, & Daffurn, 1995). Several subsequent studies have found conflicting evidence to support the effectiveness of the system in reducing cardiac arrests (Al-Qahtani et al, 2013;Chan, Jain, Nallmothu, Berg, & Sasson, 2010;DeVita et al, 2004;Hillman et al, 2005). However, many studies have also associated RRSs with decreased hospital mortality and intensive care unit (ICU) admissions (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Few studies, however, have explored the barriers to effective implementation of a RRS system. DeVita et al (2004) propose five potential barriers affecting the successful implementation of the RRS, two of which are of interest here: (1) failure to view errors as a product of the RRS rather than individual mistakes;…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of such warning signs prompted the creation of rapid response systems (RRS) to allow for rapid evaluation and treatment of any patient meeting predetermined criteria for clinical instability. Individual centres with these systems have reported significant decreases in hospital cardiac arrests and mortality in adult and paediatric patients 14 15 16 17 18 19. However, the only randomised multicentre study showed no difference in mortality or cardiac arrests between groups 20.…”
mentioning
confidence: 99%